Rethinking the Role of Grain Banks in China’s Agriculture - Teng Li; Deyi Zhou; Amar Razzaq; Qing Wang (Agriculture, 2021)
Grain banks are an organizational innovation and unique phenomenon in China that help reduce food losses and food security costs. It collects scattered food from the farming community into centralized storage and circulates it, thereby realizing asset mobilization and appreciation. This article first elaborates on the definition, function, and evolution of China’s grain banks through a literature review. Then, we used survey data of face-to-face interviews and field visits to a grain bank company in Hubei Province to analyze the economic rationale of grain bank development, including micro and macro conditions of grain bank development and its operating mechanisms. In addition, from the perspective of key stakeholders such as farmers, grain bank companies, and the government, we also studied the challenges of grain banks. We found that, in addition to providing many economic and social benefits in the form of food security and improved farmer income, grain banks still face many challenges in the new era. These include the ambiguity of property rights, lack of institutional structure, low efficiency of state-owned grain banks, and exploitation of loopholes by grain dealers. We propose to implement the supply-side reforms, clarify property rights, improve the supervision and management of grain banks, promote the privatization of grain banks, and take advantage of rural finance to realize the industrialization of the whole sector.